Gender and perceived organizational support as moderators in the relationship between role stressors and workplace bullying of targets - Harlos, Karen; Gulseren, Duygu; O'Farrell, Grace; Josephson, Wendy; Axelrod, Larry; Hinds, Aynslie; Montanino, Cassandra (Frontiers in Communication, 2023)
Previous research suggests that role stressors (role ambiguity, role conflict, role overload) are risk factors for workplace bullying, but little is known about when and for whom role stressors affect the risk of being bullied at work. These studies provide a first empirical examination of gender and perceived organizational support (POS) as moderators among targets in role stressor–bullying relationships. We propose that each role stressor relates positively to workplace bullying. We also propose that women experience higher levels of workplace bullying than men and that role stressors relate to workplace bullying more strongly for women than men. We hypothesize that POS relates negatively to workplace bullying and further, that POS has a buffering effect with role stressor–bullying relationships being weaker when POS is high. We propose that the two-way interaction of role conflict and POS is further moderated by gender; specifically, women experiencing high role conflict and low POS are especially likely to be bullied. Data collected in two cross-sectional surveys 3 years apart from a Canadian provincial education association (Study 1; n = 2,142; Study 2, n = 2,008) showed across both studies that role conflict was the strongest predictor of workplace bullying, followed by role ambiguity, and that POS was negatively related to bullying. Results partially supported gender moderation of the role conflict–bullying relationship; both studies showed higher bullying of both women and men under high role conflict, and in Study 1 women were targeted most but in Study 2 men were targeted most. POS moderated role stressor–workplace bullying relationships across both studies. High POS had its strongest buffering effects for role ambiguity and role conflict across both studies, with partial support for role overload in Study 2. Although the three-way interaction was not supported, Study 2 demonstrated higher bullying for both genders under high role conflict and low POS; however, bullying was highest for men, not women. Results affirm the importance of moderators in role stressor–bullying relationships, suggesting that POS can offset negative impacts of these stressors and that gendered bullying risk in stressful work environments warrants closer scrutiny.